Pengembangan Aplikasi Game Edukasi Matematika SD 02 Pagi Pondok Labu Berbasis Android dengan Metode Rapid Application Development Menggunakan Adobe Flash CS6 - Manik, Jonatan; Faizah, NM; Ginting, Winton (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
This research was conducted at SD 02 Pagi Pondok Labu, Cilandak, South Jakarta, with a background of the problem, namely the learning process used in education today where computer-based learning media is only limited to transferring paper media to digital media with the same appearance. This is what causes the learning media to be less than optimal as is the case in the mathematics learning process where the media used in learning material about mathematics in elementary schools is less attractive because of the learning process that still uses classical methods or conventional methods in the teaching and learning process. This research method uses the Rapid Application Development (RAD) method while the data collection methods used are observation, interviews, and literature study. This study aims to design and build learning media applications in the form of Android-based math educational games. The results of the research are in the form of a mathematics educational game application at Pondok Labu 02 Pagi Elementary School that can be played with a smartphone or laptop as a medium to increase interest in learning for students and media for teachers in providing learning about mathematics.